Total Femoral Replacement as a Salvage Operation for the Treatment of Massive Femoral Bone Loss During Revision Total Hip Arthroplasty. Issue 5 (May 2018) - DeRogatis, Michael J.; Issack, Paul S.
Abstract : Revision hip arthroplasty is being performed with increasing frequency in the United States. One of the major challenges during these procedures is addressing associated femoral bone loss. Varying degrees of proximal metaphyseal and diaphyseal bone loss may be treated with reconstruction techniques involving extensively porous-coated stems, distally based modular stems, and proximal femoral replacement. When diaphyseal bone loss extends beyond the isthmus of the femur with little support for a stem, reconstruction with replacement of the entire femur, hip, and knee (total femoral replacement) may be indicated. Total femoral replacement is best indicated for older patients with massive loss of bone stock that makes them unsuitable for less-extensive reconstruction methods. The procedure is technically demanding and is associated with a high risk of complications, including major blood loss, deep infection, dislocation, and mechanical implant failure. In appropriately selected patients, total femoral replacement can provide a successful salvage of an otherwise unreconstructible femur. (Previously, the only options available in such cases were nonoperative treatment, resection arthroplasty, or amputation.) In several case series, total femoral replacement has demonstrated good pain relief and improved function at intermediate to long-term follow-up.